Penguatan Spritual Masyarakat Perumahan Puri Taman Sari Kelurahan Borong melalui Pengajian Lorong (PELOR): Spritual Strengthening of the Puri Taman Sari Residential Community Borong District through Lorong Reaction (PELOR) - Rosmita, Rosmita; Nasaruddin, Nasaruddin (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2025)
The Lorong Recitation Activity (PELOR) is presented as a strategic program of the Makassar City Government, namely "Strengthening the Faith of the People". Lorong Recitation aims to strengthen the spiritual life of Lorong residents through teaching religious sciences such as teaching the Koran, strengthening faith and other jurisprudential sciences. This activity is carried out every week for approximately 9 months from February to November 2024. At the last meeting, this activity became even more lively with the provision of free health therapy by the Makassar Fohoway therapist team at the initiation of the missionary on duty. The results of the activity were successful in bringing in 20 participants and trying to follow up in the form of regular monthly recitations. The evaluation results showed that several weeks of activities did not take place due to participants being busy with other activities, coinciding with ELECTION week and unfavorable weather, including many moments of collective leave. The solution increases the motivation of the participants to be better able to manage their time in participating in these activities.